EFEK ROSELLA MERAH KERING TERHADAP KADAR MDA SERUM TIKUS STRAIN WISTAR YANG DI PAPAR ASAP ROKOK - Novera Herdiani; Wiwik Afridah (UNUSA Press, 2017)
Abstract: Cigarette smoke contains free radicals. Currently the number of smokers in Indonesia arestill high. This study aims to analyze the effects of red rosella of dried on the prevention of theincrease of Malondialdehyde (MDA) serum of strain wistar rats exposed to cigarette smoke. Thetotal sample of 24 male rats and divided into four groups: negative control, positive control, treatment of red rosella on dried dose 540 mg/bw, and red rosella on dried dose 810 mg/bw. Negativecontrol only given with standard feed. Positive control given by standard feed and exposed to 2cigarettes a day. Treatment group were feed by standard and red rosella of dried in the morning andexposed to 2 cigarettes after that. This study was conducted for 21 days. At the end of the study,blood serum was analyzed to determine MDA. The results of the study of MDA serum test isanalyzed with One Way ANOVA and followed by Tukey LSD test at 5% level. The giving of redrosella on dried dose 540 mg/bw and red rosella on dried dose 810 mg/bw can significantly preventthe increase of MDA serum in strain wistar rats exposed to cigarette smoke.